Science, Belief and Society 2019
DOI: 10.1332/policypress/9781529206944.003.0008
|View full text |Cite
|
Sign up to set email alerts
|

Muslim Perceptions of Biological Evolution: A Critical Review of Quantitative and Qualitative Research

Abstract: The topic of Muslims’ attitudes towards the theory of biological evolution has received increasing attention at the margins of the fields of public understanding of society, science communication or education and science in society. The methodology and methods employed in this work are primarily informed by research on attitudes towards evolution in the ‘West’, particularly in the US where the issue is highly politicized. Small, interview based qualitative and larger, survey based quantitative studies have exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Much of the literature about Islam/Muslims and evolution has often tended to portray Islam as a monolithic tradition and Muslims as a monolithic group (Carlisle, Hameed, and Elsdon‐Baker 2019, 146; Moran 2019). However, the Islamic tradition has been notably diverse since its early inception.…”
Section: Qadhi's Position On Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Much of the literature about Islam/Muslims and evolution has often tended to portray Islam as a monolithic tradition and Muslims as a monolithic group (Carlisle, Hameed, and Elsdon‐Baker 2019, 146; Moran 2019). However, the Islamic tradition has been notably diverse since its early inception.…”
Section: Qadhi's Position On Evolutionmentioning
confidence: 99%
“…Not only does he accept that there is scientific consensus for human evolution, he himself also accepts the existence of prehuman humanoids due to the presence of indisputable evidence (Qadhi 2013a). His solution to this perceived conflict between science and scripture is a type of human exclusionism––a position not unique to Qadhi (Everhart and Hameed 2013; Guhin 2016; Moran 2018; Carlisle, Hameed, and Elsdon‐Baker 2019)––whereby God intervened at a specific point in time. However, what is in many ways unique to Qadhi is his attempts to provide an explanation as to the different conclusions reached by theologians and scientists.…”
Section: Qadhi's Position On Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these are just two examples, discussions about Harun Yahya can be found in a wide range of sources (Edis and Bix 2004;Edis 2006;Enserink 2007;Guessoum 2009;Riexinger 2009aRiexinger , 2009bRiexinger , 2010Hameed 2010Hameed , 2015Numbers 2010;Thomas 2012;Bigliardi 2012Bigliardi , 2014aBigliardi , 2014bEdis and BouJaoude 2014;Clément 2015;Aechtner 2016;Dupret and Gutron 2016;Carlisle et al 2019;Unsworth 2019), reinforcing the assumption of Harun Yahya's high relevance. 4 However, at present, there is little existing evidence to support the idea that Harun Yahya deserves such extensive coverage.…”
Section: The Harun Yahya Enterprisementioning
confidence: 99%
“…This, in turn, saw both academics and politicians focus a significant amount of attention on Islamic creationism, its origins, and possible methods to combat its influence (Hameed ; Carlisle et al. , 135). Explicitly or implicitly, it was suggested that European Muslims were unanimously rejecting evolution.…”
mentioning
confidence: 99%